PENGARUH MODEL CARD SORTBERBANTUAN MEDIA MOLYMOOD PADA MATERI HIDROKARBON TERHADAP HASIL BELAJAR SISWA - Wati, Mila Karmila; Sahputra, Rachmat; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research aims to determine differences in student learning outcomes between students who were taught by themodel active learningtype of card sort with students who were Â taught by the method of discussion on hydrocarbon material of alkena group in class XI MIA SMAN 2 Pontianak. The research uses Quasy Experimental Designs withÂ  Nonequivalent Control Group Design. The sample of this research is the students of class XI MIA 2 as the control class and XI MIA 3 as the experimental class. Based on data analysis using U-Mann whitney test obtained Asymp. sig. value ((2-tailed) is 0,017 or Asymp. sig.((2-tailed) < 0,05, so that Ha is accepted and Ho is rejected, which means there are differences in learning outcomes between students of control class and students of experimental class on hydrocarbon material of alkane group. Learning using active learning model of card sort type gives high influence with effect size is 1,11. This indicates that learning using active learning model of card sort type can improve students' learning outcomes on hydrocarbon material of alkane group in class XI SMA Negeri 2 Pontianak.Keywords: active learning model, card sort, hydrocarbon of alkena group, learning outcomes